Learning, Challenges, And Resistance: An Ethnographic Case Study on the Experiences of Job Seekers in a Public Access Computer Lab - Jennifer Kobrin (Adult Education Research Conference, 2023)
This ethnographic case study focused on 19 job seekers in an urban public access computer lab to explore their challenges, learning, and criticality as related to digital platforms and systems.
Keywords: adult digital literacies; public access computer labs; digital skills; technology learning